Case Report of Drug-Induced Gingival Overgrowth (DIGO) in Amlodipine User at Bhayangkara Brimob Hospital - Rike Rayanti; Sylvia Angela Yasmine; How Kim Chuan; Susanna Halim (Postgraduate, University of Mataram, 2025)
Drug-induced gingival overgrowth (DIGO) is a condition where the gingiva is abnormally enlarged caused by anticonvulsant, calcium channel blocker, and immunosuppressant drugs. Amlodipine, a calcium channel blocker, is used to treat hypertension and is reported to be the first drug to cause gingival overgrowth. The prevalence of gingival overgrowth induced by calcium channel blockers including amlodipine is 6%-83%. This case report was written with the aim of presenting information on the management of DIGO treatment in hypertensive patients without drug replacement also underlines the importance of integrating science-based health education in dental care to support treatment adherence and patient literacy. The 60-year-old female patient came to the Dental Clinic of Bhayangkara Brimob Hospital with the main complaint of enlarged gums since one year ago almost throughout her mouth. Gum enlargement is slow and painless, but sometimes bleeds when brushing teeth. The patient had a history of high blood pressure and was prescribed amlodipine 10 mg once a day and routinely consumed since the last 5 years. Cleaning of supra and sub-gingival tartar, prescribing chlorhexidine gluconate 0.2% mouthwash to be swished before bedtime, and motivating the patient to continue to maintain oral hygiene. Conclusion: Amlodipine is one of the drugs that cause DIGO (Drug Induced Gingival Overgrowth). Good dental hygiene and patient education have a major role in improving the condition of gingival enlargement.